VIRTUAL ETHNOGRAPHY: A DISCUSSION OF THE TOOL’S SPECIFICITY - Hassina Benreguia (International Journal of Innovative Technologies in Social Science, 2025)
The rapid flow of online information, increased user interactivity across digital platforms and virtual communities, and their potential effects on individual identity, culture, and belonging have become an important topic for ethnographic research. This research has developed a virtual methodology of new tools to help explore how technologies shape societal behaviors. This includes understanding the influence of social media on personal opinions, as well as investigating the impact of online advertising and gaming on identity development. virtual ethnography is therefore essential for understanding the role of technology in contemporary life. This study aims to establish virtual ethnography as a new type of qualitative research that studies online communities and their interactions through interactive media. It is concerned with the impact of these interactions on lifestyles, culture, identity, and other social and ethnic data that ethnographic studies specialize in in their natural environment.